Safety and control devices for gas burners and gas-burning appliances. Particular requirements. Multifunctional controls with integral overpressure protection safety function (OPSF) for use with butane gas cartridges used in portable gas appliances Part 12, (13th October 2023) - British Standards Institution,
No abstract available